The Potential of Engay Food Enriched with Asian Scallops Flour for Dysphagia Food Alternative - Safira Firdaus; Siti Aminah; Nurrahman Nurrahman (International Journal of Advance Tropical Food, 2021)
Engay food is a Japanese term for a modified texture food for elderly people with dysphagia. The enrichment of the nutritional value of food is carried out by adding the calcium found in the scallop shells. This study aimed to investigate the chemical, physical, and sensory properties of engay food enrich with scallop shell flour. The food formulation consisted of milkfish and the addition of scallop shell flour as much as 0%, 2%, 4%, 6%, and 8% of the basic ingredients with 5 repetitions. The result showed, the best formulation of engay food from chemical, physical, and sensory was the concentration of 4% scallop shell flour with the calcium content of 0.099 mg / 100g, water content 68.97%, ash content 0.98%, fat 1.39%, protein 9.00%, carbohydrates 19.66% and contains 562 cal / 100g. L* 30.8, a* 2.4, b* 13.9, °Chroma 14.07, and °Hue 80.27 with the type of yellow-red color, cohesiveness value 0.334 J / m2, adhesion value 0.034 mJ, and gumminess value 206.176 N/m2. High calcium engay food with milkfish as the main ingredient can be used as an alternative food for elderly people with dysphagia because it meets the requirements for food categories level 4-5 based on IDDSI recommendation.